Fail safe management five rules to avoid project failure - Kusek, Jody Zall 1952-; Hamilton, Billy C.; World Bank.
This book provides invaluable guidance on how to avoid the failure of interventions, whether for projects, programs, or policies. The authors note that although good design is essential, 'paying attention to details that only happen during implementation is essential in avoiding failure'. The five steps outlined are salutary, and point to the craft needed for good implementation-the range of issues which have continuously to be managed, the environment, stakeholders, resources, systems, and so on. As the authors point out, some elements are beyond the control of a project manager, but all too often it is the things that are controllable that are ignored at our peril. Good management is not sexy, but it usually makes the difference between failure and success.
Electronic reproduction.
Keywords: Business failures; Project management; Electronic books